2019
DOI: 10.1021/acsami.9b14370
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Control in Tree Structure-Based 1D Fiber Assemblies for Moisture Wicking Functionality

Abstract: One of the fundamental properties of natural systems is their water transport ability, and living systems have efficient moisture management features. Here, a unique structure, inspired by the water transfer behavior in trees, was designed for one-dimensional (1D) fiber assemblies. In this 1D fiber assembly structure, a differential capillary effect enabling rapid water transfer at the interface between traditional cotton fibers and electrospun nanofibers was explored. A tree-like structure yarn was constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Based on the fiber density, the weight content was converted into the volume content. According to the references we reported previously, 25,26 the distance between the fibers in the yarns was calculated. When calculating the distance between fibers, the solid volume fraction (SVF) of the yarn should be calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fiber density, the weight content was converted into the volume content. According to the references we reported previously, 25,26 the distance between the fibers in the yarns was calculated. When calculating the distance between fibers, the solid volume fraction (SVF) of the yarn should be calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Textiles produced from these membranes were able to pull the liquid moisture away from the skin, showing a spontaneous and directional water transport property. Mao et al 25,26 reported a corespun yarn prepared by coating cotton yarns with electrospun nanofibers. Fabrics woven by these yarns showed a good moisture-wicking function such that water could be transported outside of the cloth effectively.…”
mentioning
confidence: 99%
“…3DP techniques have been widely used in e-textiles because they can accurately and rapidly print functional complex structures [64][65][66]. For instance, Zhang et al [67] fabricated a core-sheath fiber-based smart pattern on textile substrate by ink printing with a coaxial spinneret, which consisted of carbon nanotubes (CNTs) as the conductive core and silk fibroin (SF) as the dielectric sheath, as shown in Figure 3a.…”
Section: Electronic Textilesmentioning
confidence: 99%
“…Cai et al (Fan et al 2020)prepared a 3D transport fabric with advanced water transport property by coating discontinuous hydrophobic pattern on inner side and discontinuous superhydrophilic pattern on outer side. Qin et al (Mao et al 2019)fabricated one-dimensional (1D) ber with controllable water transport performance by combining tree-like structure design and material optimization together. Unfortunately, few researches on synergistic effect of heat dissipation and water evaporation have been reported.…”
Section: Introductionmentioning
confidence: 99%